2019
DOI: 10.4103/lungindia.lungindia_101_18
|View full text |Cite
|
Sign up to set email alerts
|

The initial steps in pulmonary rehabilitation: How it all began?

Abstract: Pulmonary rehabilitation plays a vital role in improving symptom, thereby enhancing health-related quality of life in patients with chronic obstructive pulmonary disease. We here with review is highlighting the landmark changes and recommendation for pulmonary rehabilitation since inception to till date. We also discuss the utilization of oxygen therapy, various measures of exercise training, and adherence strategy recommendation for betterment of the patient performance in their activity of daily living life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Results of other studies have shown similar barriers to PR in other countries: poor referral rates, lack of perceived benefits of the program by physicians and patients, limited availability of and access to services, insufficient programs and an inadequate number of qualified health professionals and patients-related factors [ 26 30 ]. According to the literature on PR “a significant barrier to the effective utilization of pulmonary rehabilitation” in the community is the lack of patient referrals, likely due to a lack of awareness among healthcare providers of the nature and benefits of this intervention.…”
Section: Discussionmentioning
confidence: 84%
“…Results of other studies have shown similar barriers to PR in other countries: poor referral rates, lack of perceived benefits of the program by physicians and patients, limited availability of and access to services, insufficient programs and an inadequate number of qualified health professionals and patients-related factors [ 26 30 ]. According to the literature on PR “a significant barrier to the effective utilization of pulmonary rehabilitation” in the community is the lack of patient referrals, likely due to a lack of awareness among healthcare providers of the nature and benefits of this intervention.…”
Section: Discussionmentioning
confidence: 84%
“…In India, the concept of PR was adopted into COPD care probably in the 1990s in the southern part of India. However, it came into practice at the beginning of the twenty first century [35]. Nevertheless, effective implementation of PR in clinical practice in India is still lacking.…”
Section: Pulmonary Rehabilitation In India-current Scenariomentioning
confidence: 99%
“…Interestingly, PR is not limited to people with chronic lung conditions but also recommended for patients with musculoskeletal disorders and heart failure. Starting PR in the earlier stages of the disease has a greater impact on the treatment process and enhancing the patient’s quality of life ( 8 , 74 ). The modified Medical Research Council Breathlessness (mMRC) is used to assess the degree of baseline functional disability due to dyspnoea.…”
Section: Introductionmentioning
confidence: 99%
“…The most important contraindications include persistent orthopedic or unstable cardiovascular diseases, transmissible infectious diseases, unstable psychiatric conditions, and severe cognitive impairment that makes it difficult to follow instructions. Other important contraindications include severe uncontrolled anemia, limited life expectancy, severe debilitating fatigue, severe visual impairment, and inability to perform training due to other diseases ( 73 , 74 , 76 , 78 ). Table 2 shows the contraindications and indications of pulmonary rehabilitation.…”
Section: Introductionmentioning
confidence: 99%